Striatonigrostriatal Spirals in Addiction - Sivils, Andy; Wang, John Q.; Chu, Xiang-Ping (Frontiers in Neural Circuits, 2021)
A biological reward system is integral to all animal life and humans are no exception. For millennia individuals have investigated this system and its influences on human behavior. In the modern day, with the US facing an ongoing epidemic of substance use without an effective treatment, these investigations are of paramount importance. It is well known that basal ganglia contribute to rewards and are involved in learning, approach behavior, economic choices, and positive emotions. This review aims to elucidate the physiological role of the striatonigrostriatal (SNS) spirals, as part of basal ganglia circuits, in this reward system and their pathophysiological role in perpetuating addiction. Additionally, the main functions of neurotransmitters such as dopamine and glutamate and their receptors in SNS circuits will be summarized. With this information, the claim that SNS spirals are crucial intermediaries in the shift from goal-directed behavior to habitual behavior will be supported, making this circuit a viable target for potential therapeutic intervention in those with substance use disorders.